Isolation and characterization of expressed sequence tag-linked microsatellite loci for the European eel (Anguilla anguilla) - PUJOLAR CASTANER, JOSE' MARTIN; ZANE, LORENZO; MAES GE; VAN HOUDT JKJ (Molecular Ecology Resources, 2009)
A European eel (Anguilla anguilla) expressed sequence tag database consisting of 795 contigs and 4008 singletons was screened for microsatellites sequences. Primers were designed to amplify 96 repeats, of which 86 gave good quality amplification products. Twenty-eight microsatellites were selected for further microsatellite genotyping. Only two loci were found to be monomorphic; out of the 26 polymorphic loci, number of alleles per locus ranged from two to 14, while the observed and expected heterozygosities ranged from 0.05 to 0.93, and from 0.05 to 0.95, respectively. All 28 primer sets tested revealed positive amplification in American eel (Anguilla rostrata).